Hormonal-Receptors-Positive and HER2-Negative Patients with Metastatic Breast Cancer Treated with First-Line Palbociclib and Hormonal Therapy: Impact of First-Cycle Neutropenia and Dose Reduction on Therapeutic Outcome - Khaled Abd Elaziz Ahmed Elnaghi; Hosam Ali Alghanmi; Shereef Ahmed Elsamany; Fathia Almarzoki; Mohamed Elsafty; Mohammad Jaffal (Hindawi-Wiley, 2023)
Background. CDK 4/6 inhibitors with hormonal therapy are the standard first-line therapy in metastatic hormonal receptors (HR)-positive and HER2-negative breast cancer. This study aims to assess the impact of neutropenia with 1st cycle, dose reduction, HER2-low status, and other clinicopathological factors on survival outcomes with the first-line palbociclib and hormonal therapy. Patients and Methods. In this retrospective study, we recruited patients with metastatic HR-positive and HER2-negative breast cancer. Neutropenia with 1st cycle, palbociclib dose reduction in addition to different clinicopathological and survival data were checked in patients' medical records. Survival outcomes were compared according to the abovementioned factors. Results. We recruited 150 patients who received first-line palbociclib with hormonal therapy. 86% of patients developed 1st cycle neutropenia which was more common in patients with high Ki67. Dose reduction was recorded in 46.7% of patients and it was more common in patients with higher Allred scores (scores 7-8). The median progression-free survival (PFS) of the study group was 22 months. No significant difference was observed in PFS according to the 1st cycle of neutropenia or grade of neutropenia. Similarly, no difference in PFS according to palbociclib dose reduction and HER2 low status was observed. Only the Allred score and having a single site of metastasis had an independent significant relation with PFS. The median overall survival (OS) of the study group was 39 months. No significant difference was observed in OS according to the 1st cycle neutropenia, grade of neutropenia, palbociclib dose reduction, and HER2-low status. Only the Allred score and having a single site of metastasis had an independent significant relation with OS. In addition, no difference was observed in PFS and OS according to ECOG PS (2 vs. 0-1) or menopausal status. Conclusion. No significant impact of the 1st cycle neutropenia, dose reduction, having ECOG PS2, menopausal status, or HER2 low status on survival outcome was observed. Survival outcome was significantly better in patients with single metastatic sites and higher ER-Allred scores.